(untitled) (Research, Society and Development, 2020)
In this research we seek to analyze and understand the construction of knowledge about Down Syndrome, based mainly on the work of John Langdon Down and its repercussions in the 19th and early 20th centuries. This research is configured as being descriptive and fits as a study of the history of science, for that we mainly search primary sources and we also resort to secondary and tertiary sources about Down Syndrome. John Langdon Down occupies a prominent role due to significant changes in the panorama of scientific knowledge of the 19th century about Down Syndrome, as he carried out the systematization and description of the syndrome as a unique and differentiated clinical condition, disseminated ideas of care and treatments to individuals, besides contributing to the differentiation in relation to “cretinism” and other mental deficiencies. When developing his reflections, Down subsidized other works of that time contributing to the construction of scientific knowledge about the syndrome. We realized that his notes were corroborated by some and that other researchers contributed to the initial process of building knowledge about Down Syndrome. This work is part of the doctoral thesis work of the first author and will provide subsidies for an upcoming research on the construction of knowledge from the second half of the 20th century, complementing important data on the history of syndrome.